Structural evidence for a latch mechanism regulating access to the active site of SufS‐family cysteine desulfurases. Issue 3 (5th March 2020) - Dunkle, Jack A.; Bruno, Michael R.; Frantom, Patrick A.
Abstract : Type 2 cysteine desulfurases are ubiquitous and often essential in plants and microorganisms owing to their role in Fe–S cluster biosynthesis. Here, an X‐ray crystal structure of wild‐type SufS with a rotated active‐site β‐hairpin, and a global structure and sequence analysis that argues for a conserved β‐latch mechanism regulating type 2 cysteine desulfurases, are reported. Abstract : Cysteine serves as the sulfur source for the biosynthesis of Fe–S clusters and thio‐cofactors, molecules that are required for core metabolic processes in all organisms. Therefore, cysteine desulfurases, which mobilize sulfur for its incorporation into thio‐cofactors by cleaving the C α —S bond of cysteine, are ubiquitous in nature. SufS, a type 2 cysteine desulfurase that is present in plants and microorganisms, mobilizes sulfur from cysteine to the transpersulfurase SufE to initiate Fe–S biosynthesis. Here, a 1.5 Å resolution X‐ray crystal structure of the Escherichia coli SufS homodimer is reported which adopts a state in which the two monomers are rotated relative to their resting state, displacing a β‐hairpin from its typical position blocking transpersulfurase access to the SufS active site. A global structure and sequence analysis of SufS family members indicates that the active‐site β‐hairpin is likely to require adjacent structural elements to function as a β‐latch regulating access to the SufS active site.